Children of the Sun: a historical look at how pediatric light therapy shaped attitudes and behaviors toward sunbathing. (23rd September 2020) - Bax, Christina E.; James, William D.
Abstract: Today, parents are warned to protect their children from the sun's ultraviolet (UV) rays, the most preventable and leading cause of skin cancer. Yet, during the first half of the 20th century, the medical community widely extolled the health benefits of daily sunbaths for babies and children. What initially had begun as evidence‐based medical therapies to prevent pediatric diseases, specifically tuberculosis and rickets, soon took on a life of its own as physicians, public health experts, and the general public embraced sunbathing and tanning as a means to ensure health and wellbeing for children and families. Here, we trace how specific medical therapies entered mainstream pediatric medicine and, converging with societal and cultural forces, shaped attitudes and behaviors towards sunbathing that still exist today. Understanding our complex history with the sun may shed light on the current peak of skin cancer incidence and future disease development. Moreover, it may help improve how we educate parents and children about sun safety by taking into account the current social and cultural context of medical practice and health communication.